Pengaruh Konsentrat Lemon Cina (Citrus microcarpa) Terhadap Mutu Minuman Sari Buah Lemon Cina Berkarbonasi - Ega, L; Picauly, Priscilia; Sopamena, Meivijona (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to determine the effect of different concentrations of lemon cina concentrate on the quality of carbonated lemon cina juice drinks. This research used a Completely Randomized Design with treatment varying concentrate concentration treatments of 12.5 mL, 25 mL, and 37.5 mL with 3 replications. Observations were made on the chemical and organoleptic characteristics of carbonated lemon cina juice drinks, namely vitamin C, total acid, total sugar, color, taste, aroma, and appearance. Carbonated lemon cina juice drink has vitamin C (0.30-0.61 mg/100g), total acid (0.60-4.20%), total sugar (15.60-20.30), color (somewhat yellow-to yellow), taste (slightly soda-flavored), aroma (not scanted with lemon cina-smells a bit like lemon cina), appearance (not bubbly-slightly bubbly). The conclusion of this research is that the concentration of lemon cina concentrate influences the chemical and organoleptic characteristics of carbonated lemon cina juice drinks, by showing changes in the value of vitamin C, total acid, total sugar, and the hedonic quality of color, aroma, taste, and appearance.